A Report on Bryozoan Fauna of Jayakwadi Bird Sanctuary, Maharashtra, India - Swami P. S.; Devdhe G. R.; Harkal A. D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The study attempts to understand the freshwater Bryozoan fauna of the Jayakwadi Bird Sanctuary, Maharashtra, India. The samples were collected and were identified based on colony morphology and floatoblast morphometry. Seven species belonging to the genus Lophopodella, Plumatella, Rumarcanella, and Hislopia were recorded. The study added valuable information on faunal resources in the Jayakwadi Bird Sanctuary.